Governing development of regions- case of Slovakia - Rudolf Bauer; Jana Knezova; Andrej Steiner (European Regional Science Association (ERSA), 2014)
Dynamism of development and competiveness of regions, as spatially and administratively defined units, depend not only on their natural, economic, social, and territorial potential but also on quality of regional development governance. At the time of creation of the regional level of territorial management in Slovakia there was expected that by introducing this new governance level the regional governments would become strong players in the field of regional development policy and provide supra-local and sub-national public services more effectively and with better quality. The paper, in its first part, concentrates on critical assessment of the current position and performance of entrusted tasks of the regional self-governments after 12 years of their existence, particularly in terms of their real opportunities to influence integrated development of territories pursuing principles of 'good governance'. Emphasis is put on analysis of key determinants conditioning legitimacy and power of regional self-governments in the area of ensuring and coordinating regional development. Findings suggest that territorial and administrative definition of the Slovak regions for fulfilling their core mission is not optimal. Furthermore there are gaps in their competencies, financial strength, fiscal autonomy and quality of development processes. We can state that despite regional governments are responsible, pursuant to law, for the comprehensive integrative development of the region, their direct impact on economic, social and environmental development of their territories is relatively small. The current status is confronted with the focus of the European policy for the period 2014-2020 and the need to react also on this level on global challenges such as climate change, ageing, lack of renewable resources, opening disparity scissors between regions etc. The paper, in its second part, in order to achieve higher quality of governing regional development within existing legal, economic and institutional framework in Slovakia, presents the innovative model of good governance in conjunction with planning and implementation of development processes. Through the analysis of individual components of the model the set of recommendations has been elaborated with the aim of optimizing position of the regional self-government as the key actor in development of its territory having not only responsibility but also adequate conditions and tools. The paper is based on results of the three years research within the project Governance financed by the Norwegian financial mechanism.
Keywords: R58; R59; 330; good governance; regional development; regional government